Wo hu cang long - Lee, Ang, 1954-; Chang, Chen.; Fa Zeng Li; Michelle Yeoh; Peipei Cheng; Sihung Lung; Ziyi Zhang; YunFat Chow (USA Taiwan Asia Union Film & Entertainment Ltd., 2000)
The disappearance of a magical jade sword spurs a breathtaking quest for the missing treasure. Li (Chow Yun-Fat) is embittered by the loss of his jade sword, and his unrequited pursuit of Yu (Michelle Yeoh) is further complicated by the mysterious intrusion of an assassin. The identity of the assassin is gradually unveiled as another poignant tale of love begins to ravel with that of Li and Yu against the backdrop of Western China's magnificent landscape.
Two warriors in pursuit of a stolen sword and a notorious fugitive are lead to an impetuous, physically-skilled, teenage nobleman's daughter, who is at a crossroads in her life.
Du Lu Wang
Language(s): English, Turkish Subtitle(s): Turkish
Keywords: Drama; Fantasy; Thriller; Action